Produkcja: Łódzka Szkoła Filmowa - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Production: Film School in Łódź Thousands of short films (turned mainly on black & white 35 mm film raw) are preserved in Film Archives of the famous Film School in Łódź. This large and unique collection consists of the earliest documentary and fiction student film projects made by famousto-be Polish filmmakers such as: Andrzej Munk, Andrzej Wajda, Roman Polański, Jerzy Skolimowski, Krzysztof Zanussi, Zbigniew Rybczyński, Krzysztof Kieślowski, Wojciech Marczewski, Sławomir Idziak and many others. The article assesses the importance of first professional student films made in Film School in Łódź and their impact on our understanding of further way of the filmmaker and formation of his individual style.